(untitled) (Journal of Industrial and Mechanical Engineering, 2019)
Argentina, from the agronomic point of view, has adequate conditions for the development of basic inputs necessary for the production of energy from biomass; It also has great potential and comparative advantages for the production of biofuels. Likewise, it was possible to determine the ex-work price or price of the product placed in the plant increases depending on the transport distance of the raw material, which decreases the feasibility of the process (Orlandi 2017). Regarding the specific location of the plant there are several techniques and instruments for decision-making, for the detection of the area of the country that ensures greater provision of raw material for the future production of lignocellulosic bioethanol. A combination of statistics with the Global Positioning System (GPS) and advanced industrial engineering tools such as the Brown-Gibson synergistic method will allow the final location of the industrial plant.